اتجاهات طلبة الثانوية العامة في فلسطين والجزائر نحو الرياضيات في ضوء بعض المتغيرات دراسة مقارنة" - أبو عقيل, الدكتور: إبراهيم إبراهيم; عايش, الأستاذة: صباح (Sciences de l'Homme et de la Société, 2015)
هدفت الدراسة إلى الكشف عن اتجاهات طلبة الثانوية العامة في فلسطين والجزائر نحو الرياضيات في ضوء بعض المتغيرات، تألفت العينة من (290) طالباً وطالبة اختيروا بالطريقة العشوائية العنقودية، ولجمع البيانات استُخدم استبيان تم التأكد من صدقه وثباته، وكشفت النتائج ان درجة اتجاهات الطلبة كانت متوسطة على جميع مجالات الاستبيان، وتبين ايضا ان الطلبة ليس لديهم الرغبة في اكتساب مفاهيم ومهارات رياضية جديدة، وانه لا يمكن تعلم الرياضيات ذاتياً، ومن جانب آخر تبين ان هناك اتجاهات ايجابية نحو الرياضيات عند الطالبات الاناث وطلبة الفرع العلمي، في حين لم تظهر فروق بين الاتجاهات الطلبة تعزى للدولة، وفي ضوء هذه النتائج قُدمت بعض التوصيات والمقترحات.   Abstract:              The aim of this study is to explore the high school students’ attitudes towards math in Palestine and Algeria on the basis of some variables. The sample is consisted of 290 males and female students. The selected sampling method is random-stratified sampling. A reliable and valid questionnaire was distributed to collect data. Results show that the obtained students’ attitudes scores are in general average. It is clear that students do not have a desire to acquire new math concepts and skills. In addition, it is clear that students cannot learn math independently. On the other side, results show that female students and students who study Science have positive attitudes towards math. Finally, there are no significant differences between the students on the basis of nationality, the study recommended some recommendations and suggestions.